Juvenile exposure to doxorubicin alters the cardiovascular response to adult-onset psychosocial stress in mice. (2nd January 2022) - Grant, Marianne K. O.; Razzoli, Maria; Abdelgawad, Ibrahim Y.; Mansk, Rachel; Seelig, Davis; Bartolomucci, Alessandro; Zordoky, Beshay N.
Abstract: Childhood cancer survivors have a high risk for premature cardiovascular diseases, mainly due to cardiotoxic cancer treatments such as doxorubicin (DOX). Psychosocial stress is a significant cardiovascular risk factor and an enormous burden in childhood cancer survivors. Although observational studies suggest that psychosocial stress is associated with cardiovascular complications in cancer survivors, there is no translationally relevant animal model to study this interaction. We established a "two-hit" model in which juvenile mice were administered DOX (4 mg/kg/week for 3 weeks), paired to a validated model of chronic subordination stress (CSS) 5 weeks later upon reaching adulthood. Blood pressure, heart rate, and activity were monitored by radio-telemetry. At the end of CSS experiment, cardiac function was assessed by echocardiography. Cardiac fibrosis and inflammation were assessed by histopathologic analysis. Gene expressions of inflammatory and fibrotic markers were determined by PCR. Juvenile exposure to DOX followed by adult-onset CSS caused cardiac fibrosis and inflammation as evident by histopathologic findings and upregulated gene expression of multiple inflammatory and fibrotic markers. Intriguingly, juvenile exposure to DOX blunted CSS-induced hypertension but not CSS-induced tachycardia. There were no significant differences in cardiac function parameters among all groups, but juvenile exposure to DOX abrogated the hypertrophic response to CSS. In conclusion, we established a translationally relevant mouse model of juvenile DOX-induced cardiotoxicity that predisposes to adult-onset stress-induced adverse cardiac remodeling. Psychosocial stress should be taken into consideration in cardiovascular risk stratification of DOX-treated childhood cancer survivors.